Proceedings of the 2015 ACM SIGMOD International Conference on Management of Data 2015
DOI: 10.1145/2723372.2735369
|View full text |Cite
|
Sign up to set email alerts
|

Ringo

Abstract: We present Ringo, a system for analysis of large graphs. Graphs provide a way to represent and analyze systems of interacting objects (people, proteins, webpages) with edges between the objects denoting interactions (friendships, physical interactions, links). Mining graphs provides valuable insights about individual objects as well as the relationships among them. In building Ringo, we take advantage of the fact that machines with large memory and many cores are widely available and also relatively affordable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…In the last years, knowledge about gene regulation of plant differentiation has speed out and genes involved on the induction of embryogenic competence of somatic cells have been identified in woody plant species, mainly conifers (Rupps et al., 2016; Gautier et al., 2018). But, in oaks and in spite of its ecological and economical importance, very few reports have been released concerning genetic control of SE induction (Šunderlíková et al., 2009; Valladares et al., 2013) and maturation (Šunderlíková and Wilhem, 2002; Pérez et al., 2015). More recently, DNA demethylation has been associated with SE initiation in Q. alba (Corredoira et al., 2017b).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In the last years, knowledge about gene regulation of plant differentiation has speed out and genes involved on the induction of embryogenic competence of somatic cells have been identified in woody plant species, mainly conifers (Rupps et al., 2016; Gautier et al., 2018). But, in oaks and in spite of its ecological and economical importance, very few reports have been released concerning genetic control of SE induction (Šunderlíková et al., 2009; Valladares et al., 2013) and maturation (Šunderlíková and Wilhem, 2002; Pérez et al., 2015). More recently, DNA demethylation has been associated with SE initiation in Q. alba (Corredoira et al., 2017b).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…come at the price of higher communication cost and increased system complexity [71]. Moreover, sometimes distributed solutions cannot be used either due to financial or privacy-related constraints.…”
mentioning
confidence: 99%
“…Centralized architectures, in contrast, do not have network costs, are commonly affordable, and provide enough resources to load all-but-the-largest graphs. Some centralized storage engines have demonstrated that they can handle large graphs, but they focus primarily on supporting one particular type of workload (e.g., Ringo [71] supports graph analytics, RDF engines like Virtuoso [67] or RDFox [60] focus on SPARQL [39]). To the best of our knowledge, we still lack a single storage solution that can handle very large KGs as well as support multiple workloads.…”
mentioning
confidence: 99%
“…First, the typical memory capacities of the fast and slow memories keep diverging, resulting in increasingly higher slow-to-fast capacity ratios. Memory-intensive big-data applications like neural networks [38], [44], [46], [47], genome alignment [18], [19], [39], and graph analytics [22], [58], [61], [71], [73] have been continuously driving the growth of main memory capacity. The emerging NVM technologies, such as phase-change memories [78] and Intel 3D XPoint [29], promise to handily extend the byte-addressable memory in a system to TB scales.…”
Section: A Trends Of Hybrid Memory Systemsmentioning
confidence: 99%